THEORETICAL BASIS OF THE SYNTHESIS OF EUROPEAN AND UZBEKISTAN NOVEL TRADITIONS - Yulduz Ziyayeva (Journals Park Publishing, 2025)
The article provides a detailed consideration of the theoretical foundations of the synthesis of European and Uzbek novelist traditions. The features characteristic of the artistic perception and reflection of the world and man in European literature are studied using the example of the analysis of novels. Also, the traditions of folk oral and written literature in Uzbek novelist are studied.
Keywords: Novel, novel plot, image and imagery, European novelist traditions, folk oral traditions, written literary traditions, synthesis, symbolism, figurative narrative method.